Impact of stress-induced hyperglycemia on the outcome of children with trauma: A cross-sectional analysis based on propensity score-matched population - Tsai, Yi-Wen (Sci Rep, 2019)
This was a retrospective study of pediatric trauma patients and were hospitalized in a level-1 trauma center from January 1, 2009 to December 31, 2016. Stress-induced hyperglycemia (SIH) was defined as a hyperglycemia level ≥200 mg/dL upon arrival at the emergency department without any history of diabetes or a hemoglobin A1c level ≥6.5% upon arrival or during the first month of admission. The results demonstrated that the patients with SIH (n = 36) had a significantly longer length of stay (LOS) in hospital (16.4 vs. 7.8 days, p = 0.002), higher rates of intensive care unit (ICU) admission (55.6% vs. 20.9%, p < 0.001), and higher in-hospital mortality rates (5.6% vs. 0.6%, p = 0.028) compared with those with non-diabetic normoglycemia (NDN). However, in the 24-pair well-balanced propensity score-matched patient populations, in which significant difference in sex, age, and injury severity score were eliminated, patient outcomes in terms of LOS in hospital, rate of ICU admission, and in-hospital mortality rate were not significantly different between the patients with SIH and NDN. The different baseline characteristics of the patients, particularly injury severity, may be associated with poorer outcomes in pediatric trauma patients with SIH compared with those with NDN. This study also indicated that, upon major trauma, the response of pediatric patients with SIH is different from that of adult patients.